Conservation of carnivorous plants - Clarke, C.; Cross, Adam; Rice, B. (2018)
Approximately 20% of carnivorous plant species are threatened worldwide. Key threats include habitat degradation and loss, altered fire regimes or hydrology, and collection of plants for trade. In most parts of the world, conservation efforts are focused on documenting the threats to species, a necessary precursor to the implementation of conservation strategies and actions. To date, North America is the only region where species-specific conservation actions have been implemented. In southwestern Australia, inappropriate land management practices and urbanization threaten a number of species, whereas in Southeast Asia, Nepenthes pitcher plants are threatened by habitat destruction and collection for trade. Some iconic carnivorous plant species in these two biodiversity hotspots are critically endangered and the need for recovery plans and actions is urgent. There is an equally urgent need for baseline data on the conservation status of carnivorous plant species from other regions, particularly Africa and South America.